Comparison of the spiral and fractal ground with the traditional radial in various monopole structures - Tumaneng, Edward John R. (2006)
The use of straight wire radials and other wire geometries as substitutes to a conducting ground plane for small monopole antennas were explored. Using 4NEC2 simulations, straight radials and three different geometries were investigated namely the spiral, the meander, and the Hilbert. The effects of varying the number of wires (N=32, 16, 8, 4, 2 and 1) used and the radius of the geometries (r=82 mm, 41 mm, and 20 mm) on the input impendance, resonant frequency, and VSWR (with respect to a 50 characteristic impedance) were observed and compared to that obtained using an infinite ground plane. Based on the simulation results, the antennas that exhibit optimum performance were constructed and characterized. Simulated and actual measurements showed that a single radial, with length approximately equal to the length of the monopole, is an effective substitute to a ground plane. Utilizing the different geometries is an effective method of compressing long radials into small spaces and achieving acceptable antenna impedance and VSWR. For the 915 MHz quarter wavelength straight monopole, a spiral ground with radius of 0.0625 was obtained. The VSWR of 1.44 was obtained from this antenna.